Impact Evaluation Study for Institution Strengthening of Social Food Distribution - Notoatmojo, Budiman (Bina Nusantara University, 2016)
The general objectives of this study were to evaluate whether the implementation of activities for strengthening LDPM could achieve the expected goals, to evaluate whether the LDPM strengthening activities had a positive impact. The study analysis used was descriptive, comparison, and financial analysis. The results of this study have shown that LDPM farmers’ income have increased significantly, and the Gapoktan as LPDM farmers’ institution has been significantly developing as a Bulog function in procuring grain paddy from farmers during peak harvest and distributing rice to stabilize the price of rice during the limited rice in the market.